6xy-12x^2y -18xy^2
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(12x^2y-18xy^2-30y^3\)
\(=6xy\left(2x-3y-5y^2\right)\)
\(=6xy\left[-5y^2-5y+2y+2\right]\)
\(=6xy\left[-5y\left(y+1\right)+2\left(y+1\right)\right]\)
\(=6xy\left(y+1\right)\left(2-5y\right)\)
\(\left(2x-y\right)^3=\left(2x\right)^3-3\left(2x\right)^2y+3\cdot2x\cdot y^2-y^3\\ =8x^3-12x^2y+6xy^2-y^3\)
Chọn \(12x^2y\)
b, \(12x^2y-18xy^2-30y^3\)
\(=6y\left(2x^2-3xy-5y^2\right)\)
a,
$xy^2+x^2y+(-2xy^2)=xy^2-2xy^2+x^2y=-xy^2+x^2y$
b,
$12x^2y^3z^4+(-7x^2y^3z^4)=12x^2y^3z^4-7x^2y^3z^4=5x^2y^3z^4$
c,
$-6xy^3-(-6xy^3)+6x^3=-6xy^3+6xy^3+6x^3=0+6x^3=6x^3$
d,
$\frac{-x^2}{2}+\frac{7}{2}x^2+x=(\frac{7}{2}-\frac{1}{2})x^2+x$
$=3x^2+x$
e,
$2x^3+3x^3-\frac{1}{3}x^3=(2+3-\frac{1}{3})x^3=\frac{14}{3}x^3$
f,
$5xy^2+\frac{1}{2}xy^2+\frac{1}{4}xy^2=(5+\frac{1}{2}+\frac{1}{4})xy^2$
$=\frac{23}{4}xy^2$
`8x^3 - 12x^{2} y + 6xy^2 - y^3 + 12x^2 - 12xy + 3y^2 + 11`
`=(8x^3 - 12x^{2}y + 6xy^{2} - y^{3}) + 3(4x^2 - 4xy + y^2) + 11`
`=(2x-y)^{3} + 3(2x-y)^2 + 11`
Thay `2x-y=9` vào `:`
`9^3 + 3 . 9^2 + 11`
`=729 + 243 + 11`
`=983`
A=8x^3-12x^2y+6xy^2-y^3+12x^2-12xy+3y^2+11
=(2x-y)^3+4(2x-y)^2+11
Khi 2x-y=9 thì A=9^3+4*9^2+11
=1064
\(6xy-12x^2y-18xy^2\)
\(=6xy\left(1-2x-3y\right)\)